Response to the Second TNF-α Inhibitor (Adalimumab or Infliximab) after Failing the First One in Refractory Idiopathic Inflammatory Retinal Vascular Leakage. (4th July 2022) - Maleki, Arash; Garcia, Cristina M; Asgari, Soheila; Manhapra, Ambika; Foster, Charles Stephen
ABSTRACT: Purpose: To determine the response to the second TNF-α inhibitor (adalimumab and infliximab) after failing the first agent in idiopathic inflammatory retinal vascular leakage. Materials and Methods: This was a retrospective observational case series. Patients with the diagnosis of idiopathic inflammatory retinal vascular leakage who had received both infliximab and adalimumab were included in the study. Results: Twelve and 15 patients received adalimumab (Group one) and infliximab (Group two) as the first treatment, respectively. The remission rates between Group one (58.3%) and Group two (66.7%) were not statistically significant. ( P = .4) As the second agent, adalimumab was more effective in younger patients (27.5 ± 20.6) compared to older patients (48.75 ± 10.2). ( P = .03). Moreover, patients with lower vision responded marginally better to infliximab as the second treatment ( P = .06). Conclusion: Either TNF-α inhibitor, adalimumab and infliximab, can be employed in the treatment of the patients with idiopathic inflammatory retinal vascular leakage who fail one of these agents.